Kualitas Pelayanan, Harga dan Lokasi terhadap Kepuasan Konsumen pada Rumah Sakit Mitra Sejati - Boby Sianturi; Verina Astria BR Ginting; Loviga Emia BR Karo; Rintan BR Saragih; Holfian Daulat Tambun Saribu (IPM2KPE, 2024)
This research aims to examine the influence of service quality, price and location on consumer satisfaction at Mitra Sejati Hospital. The research method used is a quantitative method with a positivistic approach, which involves collecting and analyzing data in the form of numbers to produce concrete conclusions. The research results show that service quality, price and location have a positive and significant influence on consumer satisfaction. This is proven through statistical tests with the Sig t value which shows the influence of service quality on consumer satisfaction (0.014 < 0.05), price on consumer satisfaction (0.013 < 0.05), and location on consumer satisfaction (0.001 < 0.05 ). Apart from that, the F test also shows that simultaneously, service quality, price and location together have a significant effect on consumer satisfaction. Conclusion, that the importance of service quality management, setting the right price, and choosing a strategic location in increasing consumer satisfaction at Mitra Sejati Hospital. Keywords: Price, Customer Satisfaction, Service Quality, Location